2004
DOI: 10.1007/s10552-004-1484-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent increase in cancer survival according to age: higher survival in all age groups, but widening age gradient

Abstract: A major increase in long-term survival of cancer patients in the 1990s has recently been demonstrated. It is unclear, however, to what extent this increase has been shared by cancer patients at various ages. Using the 1973-2000 data base of the Surveillance, Epidemiology, and End Results programme, recent increase in 10-year relative survival of cancer patients in the US was assessed for 4 major age groups and 15 major cancer sites by comparing results of a period analysis for the 1996-2000 period with results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 42 publications
0
15
0
2
Order By: Relevance
“…Recent analysis documents a major increase in the 10 year survivorship for many common cancers in the US compared to the late 1980's, thus more individuals may be exposed to TKIs and other molecule-targeted therapeutics for longer durations (Brenner and Arndt, 2004). Although overall, the side-effects of targeted therapies such as the TKIs are well-tolerated compared to older chemotherapeutic drugs, our results indicate that, as with Herceptin therapy, cardiovascular function should be closely monitored with chronic exposure to EGFR TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis documents a major increase in the 10 year survivorship for many common cancers in the US compared to the late 1980's, thus more individuals may be exposed to TKIs and other molecule-targeted therapeutics for longer durations (Brenner and Arndt, 2004). Although overall, the side-effects of targeted therapies such as the TKIs are well-tolerated compared to older chemotherapeutic drugs, our results indicate that, as with Herceptin therapy, cardiovascular function should be closely monitored with chronic exposure to EGFR TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, among cancer survivors, the most common primary carcinoma is female breast cancer (22%), followed by prostate cancer (17%), colorectal cancer (11%), and gynecologic cancers (10%). Ten-year relative survival rates lag among those who are older, with SEER estimates for 1996-2000 indicating overall survival rates of 66.1%, 58.8%, 56.3% and 47.1% for age groups of 15-54, 55-64, 65-74 and 75+ years, respectively [7]. In addition, while increases in 10-year survival have ranged from 7.4 to 10.4% among those aged 15-74 years, increases of only 3.0% were noted among cancer patients who were older, thus indicating that the age gradient in survival has either persisted or widened.…”
Section: Description Of the Populationmentioning
confidence: 99%
“…Because they are advanced in age, older patients may also receive less aggressive treatment, independent of comorbidity. 41,42 We compared our estimates for 5-year relative survival with those reported for primary liver cancer in Canada by the Canadian Cancer Society for 2006-2008. 5 We found that our estimates for 5-year relative survival in both sexes aged 80 years or older in Ontario were slightly higher: Canadian Cancer Society estimates for 5-year relative survival in female patients given a diagnosis at ages 60-69, 70-79 and 80-99 years were 21.0% (95% CI 15.0%-28.0%), 12.0% (95% CI 7.0%-18.0%) and 7.0% (95% CI 3.0%-13.0%), respectively; estimates for 5-year relative survival in male patients given a diagnosis at ages 60-69, 70-79 and 80-99 years were 22.0% (95% CI 18.0%-26.0%), 16.0% (95% CI 12%-19.0%) and 6.0% (95% CI 3.0%-11.0%), respectively.…”
Section: Cmaj Openmentioning
confidence: 99%